Experiential learning in HE and implications for student volunteering - Konidari, Stavroula (Centre for Professional and Educational Development, London Metropolitan University, 2022)
A study on the impact of volunteering on university students in London found that students that volunteer benefit from it. Volunteering brings students into contact with the wider community, strengthens their ties with their institution and builds skills, employability, and opportunities for personal development (viz Education for Social Justice Framework [ESJF], 2019).This paper presents a critical review of experiential learning in HE, by exploring the roles of students and practitioners with reference and application to my own prior professional area of student volunteering and its implications with a focus on London Met and education for social justice.